L’ospitalità negata e il disfacimento di una società: i casi emblematici di Lot a Sodoma in Gn 19 e del crimine di Gabaa in Gdc 19 - Rizzi, Giovanni (The Biblical Annals, 2023)
Hospitality is a widespread practice in the ancient Near East, also regulated by written legislation. Biblical legislation protects the orphan, the widow and the foreigner; but there is also an opposite tendency of not being able to accept the presence of pagan populations in the land of the fathers. The protocol of hospitality is a practice in the biblical world which never reached the form of written legislation, and which is presented as a set of literary motifs disseminated in numerous texts, without configuring a true and proper literary genre. The stories of Gen 19:1–29 and of Judg 19:11–30 are influenced by the dialectic between the two tendencies of the biblical world; what emerges from their comparison is the warning that the violation of the protocol of hospitality is an indication of the unravelling of the society. A canonical reading of the two biblical stories proposes as an example the behaviour of Abraham, who practices unconditional hospitality without limits.